RESEARCH TRENDS IN INTELLECTUAL CAPITAL AND UNIVERSITY PERFORMANCE A BIBLIOMETRIC ANALYSIS USING SCOPUS DATABASE - Cicik Suciati; Sigit Hermawan (Antis Publisher, 2024)
General Background: Intellectual capital plays a pivotal role in enhancing the performance and competitiveness of universities, influencing their reputation and success. Specific Background: While much research has been conducted on intellectual capital, its relationship with university performance remains a topic of ongoing inquiry, requiring comprehensive bibliometric analysis to identify trends and knowledge gaps. Knowledge Gap: Previous studies have often focused narrowly on intellectual capital without a holistic consideration of university performance metrics, leaving room for further exploration. Aims: This study aims to evaluate the relationship between intellectual capital and university performance by analyzing publications indexed in Scopus from 2014 to 2023, using bibliometric analysis to uncover trends, authorship patterns, country contributions, and keyword usage. Results: The analysis of 211 publications revealed that Italy and Indonesia are the leading countries in this field, with